Conflicting goals and obligations: Tensions affecting communication in pediatric oncology. Issue 1 (January 2022) - Sisk, Bryan A.; Schulz, Ginny; Kaye, Erica C.; Baker, Justin N.; Mack, Jennifer W.; DuBois, James M.
Highlights: The authors performed 10 focus groups with 59 pediatric oncology professionals. Clinicians indicated 5 themes of tensions that interfered with communication goals. A framework of justificatory conditions might help if communication goals conflict. Abstract: Objectives: To describe the tensions experienced by clinicians and psychosocial professionals that affect communication in pediatric oncology. Methods: Ten focus groups with nurses, nurse practitioners, physicians, and psychosocial professionals at 2 US institutions. We analyzed transcripts using thematic analysis, assessing tensions experienced when communicating with parents. Results: We identified 5 themes of tensions, defined as challenges experienced when clinicians and psychosocial professionals are trying to achieve multiple conflicting goals or obligations while communicating: (1) Supporting parental hopes while providing honest opinions and information; (2) disclosing all possible outcomes while avoiding the creation of new worries or uncertainties; (3) building relationships while maintaining personal boundaries; (4) disclosing sensitive information while adhering to professional role and perceived authority; (5) validating parental beliefs or decisions while fulfilling obligation for honesty. Some tensions represented conflicts between different communication goals. Others represented conflicts between a communication goal and another obligation. Conclusion: Clinicians and psychosocial professionals experience tensions that affect communication with parents in pediatric oncology. Some tensions might be addressed with interventions or education. Others will require further analysis to provide sufficient guidance to clinicians. Practice implications: Unaddressed tensions might lead to poor communication and clinician burnout. Future work should explore solutions to these tensions.